Design and Application of Special Service Tools (SST) for Telescopic Front Fork - Susilawati Susilawati; Azhis Sholeh Buchori (Automotive Experiences, 2019)
Although simple, removing the front fork telescopic (TFF) seal on a motorcycle without special service tools (SST) can cause work accidents for mechanics and loss for consumers and workshops. Therefore, product development research has been carried out to design a seal remover for TFF. Then, a TRL measurement using Techno-meter was done on the prototype that has been developed. A quick measurement by Techno-meter shows that the prototype has reached level 6 (intermediate), where the prototype has been demonstrated/tested in a relevant environment. In conclusion, through continued work (reviewing products, improvising, and testing prototypes on a larger scale), this prototype promises to be mass-produced as downstream of research products to the market.